2001
DOI: 10.1034/j.1600-0404.2001.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from amyotrophic lateral sclerosis in Finland, 1986-1995

Abstract: In accordance with other countries ALS mortality in Finland is steadily increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…Mortality rates have increased in the US [12], Finland [11], Norway [10], Britain [23] and Italy [24]. Similar to our study, a more pronounced trend in women, with a decreasing sex ratio over time, has been found in the US [12], Britain [23], Norway [10] and Finland [11]. These data provide consistency of findings, not only between countries, but also between different health care systems and study designs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mortality rates have increased in the US [12], Finland [11], Norway [10], Britain [23] and Italy [24]. Similar to our study, a more pronounced trend in women, with a decreasing sex ratio over time, has been found in the US [12], Britain [23], Norway [10] and Finland [11]. These data provide consistency of findings, not only between countries, but also between different health care systems and study designs.…”
Section: Discussionsupporting
confidence: 92%
“…Reports of mortality rates mirror incidence studies and have shown that mortality from MND has increased over time in different parts of the world [10][11][12]. Although they may underestimate incidence, mortality studies based on administrative databases have the advantage of including large sample sizes during long periods, providing robust power for the examination of change over time.…”
Section: Introductionmentioning
confidence: 98%
“…Lastly, in this study, 4 patients originally diagnosed as having ALS had MS recorded as the main cause of death, and 1 patient had both MS and MND as primary causes. Of 29 studies, 12 used both primary and secondary causes of death, 6 used only primary causes [12] and 11 did not include that information [15,59,60] .…”
Section: Mortality Data Should Be Based On Underlying and Contributormentioning
confidence: 99%
“…Firstly, several studies have argued for an increase in incidence and mortality rates from MS [13] , ALS [14][15][16][17][18] , and PD [19][20][21] in Western countries during the second half of the last century. Whether the trends in the time series might be due to predisposing factors, or, rather, to immediate factors (such as change of registration practice), is an issue open to further analysis.…”
Section: Introductionmentioning
confidence: 99%